Building Information Modelling as an Opportunity and Risk for Stakeholders Involved in Construction Investment Process. (2017) - Grzyl, Beata; Miszewska-Urbańska, Emilia; Apollo, Magdalena
Abstract: The requirements to apply Building Information Modelling (BIM) in public investments worldwide are currently very high. Significant interest (sometimes formulated also as a requirement) in BIM technology can be observed also among private investors. Design technology that applies BIM is supported by many private investors due to its numerous advantages. A growing group of construction designers (steel, concrete and reinforced concrete among others) and installation designers, producers of prefabricated elements (steel and reinforcements), engineers, architects, construction companies, developers, contract managers and investors in Poland and worldwide notices opportunities offered by using BIM technology in preparation and construction phase, as well as building management. At the same time experts in construction industry draw attention to the low level of competitiveness of Polish construction companies in global and European market caused, among others, by insufficient application of modern technology and innovation, as well as lack of public investor's initiative in promoting the application of BIM. It is difficult to assess the level of BIM implementation in Polish companies (due to lack of wider research results). The goal of this paper is to present the results of initial research regarding the level of knowledge of BIM and the scope of its implementation in Polish construction companies. The goal of the research was also to establish the level of interest and ability to implement BIM by public investors, architecture and construction companies. The paper also presents the scope of actions undertaken by the state, in the context of public investments using BIM.